Diagnostic Accuracy of Stereotactic Brain Biopsy of 32 Brain Tumor Cases - Raihan, Md Zahid; Chowdhury, Sharif Md Norman Khaled; Ara, Sayeda Asfiya; Sarkar, Mainul Haque; Hossain, SK Sader (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: brain biopsy; frame-based biopsy; stereotactic DOI: 10.3329/jcmcta.v20i2.5622 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):24-28